Education, Skills, and Labor Market Outcomes : Results from Large-Scale Adult Skills Surveys in Urban Areas in 12 Countries - Roseth, Viviana V.; Valerio, Alexandria; Gutierrez, Marcela (World Bank, Washington, DC, 2016)
In recent years, skills development has become a priority among developed and developing countries alike. The World Bank Group, in its quest to end extreme poverty and promote shared prosperity, has joined efforts with countries and multilateral development partners to ensure that individuals have access to quality education and training opportunities and that employers can find the skills they need to operate. The skills towards employability and productivity (STEP) skills measurement program is part of the World Bank’s portfolio of analytical products on skills. The STEP program consists of two survey instruments that collect information on the supply and demand for skills in urban areas: a household survey and an employer survey. STEP has been implemented in waves, the first surveys being implemented in seven countries in 2012 (Bolivia, Colombia, Ghana, Lao Peoples Democratic Republic (PDR), Ukraine, Vietnam, and the Yunnan Province in China), and the second in five countries in 2013 (Armenia, Azerbaijan, Georgia, Kenya, and Macedonia, Former Yugoslav Republic of (FYR)). The data presented in this publication correspond to these countries. It illustrates the similarities and differences among groups that have completed different education levels on a wide range of issues and outcomes. Section one analyzes the trajectory of skills acquisition: participation in early childhood education programs, educational attainment by gender, and participation in training and apprenticeship programs. Section two explores background conditions associated with educational attainment, including the socioeconomic status of survey respondents at age 15, the educational attainment of their parents, their households’ asset levels, their health (as expressed by the presence of chronic illness), and their overall satisfaction with life. Section three covers cognitive skills: writing, numeracy, and reading (which is also evaluated through a direct reading assessment). Section four covers job-relevant skills, which are task-specific and which respondents possess or use on the job; and section five covers socio-emotional skills, using established metrics to measure personality and behavior. Section six covers the status of survey respondents in the labor market: whether they are employed, unemployed, or inactive.